2015
DOI: 10.1002/cyto.b.21245
|View full text |Cite
|
Sign up to set email alerts
|

Combined accurate platelet enumeration and reticulated platelet determination by flow cytometry

Abstract: Background: Diagnosing the cause of thrombocytopenia often requires a bone marrow aspiration or biopsy, an invasive procedure. Reticulated platelets (RP) are immature RNA containing platelets, accurate RP enumeration has yet to be achieved, partially due to the lack of a robust reference method. Goal: To refine previous work and gating strategies distinguishing RP from mature platelets while incorporating accurate platelet enumeration into the analysis. After reviewing previously published studies on Thiazole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…The use of fluorescence probes, in particular fluorescence-labelled antibodies, can provide information on the abundance of specific molecular components of cells and their functional physiology. Platelets represent the smallest “cellular” material that most flow cytometers were generally designed to detect, and multicolor flow cytometry is a useful tool for the characterization of platelets and their receptor repertoires (6). …”
Section: Introductionmentioning
confidence: 99%
“…The use of fluorescence probes, in particular fluorescence-labelled antibodies, can provide information on the abundance of specific molecular components of cells and their functional physiology. Platelets represent the smallest “cellular” material that most flow cytometers were generally designed to detect, and multicolor flow cytometry is a useful tool for the characterization of platelets and their receptor repertoires (6). …”
Section: Introductionmentioning
confidence: 99%
“…No adverse side effects were encountered. Platelet numbers in this patient rose from 36 × 10 9 /L to 85 × 10 9 /L, and fell within the normal range . Concordantly, T regs increased from 3.5% of CD4 T cells to 10.2% after 2 weeks of IL‐2 treatment and stabilized at 9% by the end of treatment.…”
Section: Immunologymentioning
confidence: 61%
“…Many studies showed that RP measurement is a non-invasive test that represents a surrogate marker for megakaryocytic activity [13][14][15][16][17][18][19][20][21] . Therefore, the current study aimed to evaluate the RP% in patients with chronic hepatitis C as an index of platelet production and to evaluate the relationship between the RP% and the platelet count in those patients.…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometric analysis had been considered the preferred method of measuring RP [14,15] . Thiazole orange (TO), a nucleic acid dye, [16][17][18] remains a good choice for RP staining [15] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation